The efficiency of the active controlled rectifier operation in the mains voltage distortion mode - Krylov, D. S.; Kholod, O. I. (Національний технічний університет "Харківський політехнічний інститут", 2021)
Checking the efficiency of the active rectifier with differences types of control systems in conditions of deep voltage distortions of a three-phase three-wire supply network. Methodology. The authors have used the Matlab/Simulink software environment to create a model of an active rectifier with various types of control systems as part of a frequency electric drive. We performed a series of simulations of the operating modes of an active rectifier with various control systems when the supply voltage is distorted. Results. When the active rectifier is operating in an unregulated mode, the distortions of the current and mains voltage exceed the maximum permissible values. The quality indicators of the mains current and mains voltage are significantly higher than the normally permissible values. In the absence of voltage distortions in the supply network, the operation of the active rectifier can effectively eliminate the distortions of the mains current, regardless of the type of control system of the active rectifier. In conditions of deep distortions of the supply network voltage, the operation of an active rectifier with a vector control system is more efficient than with a parametric control system. Originality. Criteria for determining the quality of consumed electricity at the connection point of the circuit are proposed. Practical significance. Recommendations have been developed for the use of active rectifier control systems when working with a distorted power supply voltage.

Розглянуто роботу активного керованого випрямляча-джерела напруги (АВДН) з параметричною та векторною системами управління, які працюють з фіксованою частотою модуляції в складі електроприводу потужністю 315 кВт паралельно з іншими навантаженнями в умовах спотворення напруги джерела живлення. Виконано математичне моделювання АВДН з різними системами управління. Запропоновано критерії визначення якості споживаної електроенергії в точці підключення схеми. Розроблено рекомендації щодо використання систем управління АВДН при роботі зі спотвореною напругою джерела живлення.
Keywords: active rectifier; vector control system; parametric control system; PWM frequency; mains voltage distortion; mains current distortion; total harmonic distortion; активний випрямляч; векторна система управління; параметрична система управління; частота ШІМ; спотворення напруги мережі; спотворення струму мережі; сумарний коефіцієнт гармонійних спотворень